INTERAKSI Ag DENGAN SUPERKONDUKTOR BSCCO FASA 2223 - Purwamargapratala, Yustinus; Adi, Wisnu Ari (MESIN, 2006)
Interaction Ag with 2223phaseBSCCO superconductor. The addition o/Ag20 (0, 2.5, 5, and10 wt%Ag) to matrix of2223 phase BSCCO superconductor that sintered at 845 oCfor 72 hours in air have beeninvestigated. The Agadditions promote thedecomposition of2223phasesto 2212phasesBSCCO andcausedpresent some impurities phases. The impurities areproducted bythe Agaddition ableto be usedas effectivelypinning sources to hold vortex (flux line) movement. The Tcmeasurement results are 111 K, 107 K, 105 K,and103Kwith addition ofO, 2.5, 5, and10 wt%Ag respectively. The Jc measurement results are 3.6xl(f,5.6x1(f, 6.9x1(f, and U.8xl(fAm2 with addition ofO, 2.5, 5, and 10 wt%Ag respectively. From theXRDanalysis shown that the addititon ofAg caused peaks of 2212phases BSCCO are clearly visible and thesamples contain some impurities phases (CuO, Ca^CuO^, dan CajPbOJ. From the SEM analysis shown thatthe addititon ofAg should lead to a slight increase of the plate like grain size of 2223phase BSCCO withincreasing Ag content. From this experiment we conclude that the Tc depress and the Jc enhance withincreasing Agcontent. The addititon ofAg should leadtoa slight increase ofthe platelike grain size of 2223phase BSCCO with increasingAg content.